Transnational Insurgency and Border Security Challenges in Lake Chad Basin: The Nigerian Perspective - Fatokun, Olalekan S.; Ibitoye, Pius O. (African Journal of Stability and Development (AJSD), 2019)
Border security management and defence are crucial to any measure that seeks to check effectively, transnational insurgency and other forms of cross-border criminalities in any part of Africa. However, addressing the issue of porosity of international boundaries, which in most parts allows unhindered movement of people and goods across the boundaries, has become a greater challenge for Lake Chad Basin Countries, especially, Nigeria, Cameroun, Niger and Chad. The fragility of the basin countries security systems and porous borders allowed for armed groups and common banditry to flourish. Thus, these areas have become the routine of Boko Haram terrorist, armed bandits and other criminals along borders. This study, therefore, examines transnational insurgency and border security challenges in Lake Chad basin, focusing on the Nigerian perspective. The study employs both primary and secondary sources of data collection and adopts a descriptive method for analysis. The study establishes the nexus between transnational insurgency and border security, while findings reveal that the inability of border security agencies to monitor and defend Nigerian borders are not unconnected to various challenges that are confronting these security agencies in particular, and the general insecurity that enveloped the Lake Chad Basin areas. Recommendations were made based on the findings of this study.